2008
DOI: 10.1159/000135711
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Arrhythmias after Subarachnoid Hemorrhage: Risk Factors and Impact on Outcome

Abstract: Objective: Serious cardiac arrhythmias have been described in approximately 5% of patients after subarachnoid hemorrhage (SAH). The aim of this study was to identify the frequency, risk factors and clinical impact of cardiac arrhythmia after SAH. Methods: We prospectively studied 580 spontaneous SAH patients and identified risk factors and complications associated with the development of clinically significant arrhythmia. Multiple logistic regression analysis was used to calculate adjusted odds ratios for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
65
5
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(78 citation statements)
references
References 47 publications
4
65
5
4
Order By: Relevance
“…A recent study has found that arrhythmias are associated with an increased risk of cardiovascular comorbidity, prolonged hospital stay and poor outcome or death after SAH, after adjusting for other predictors of poor outcome [22]. Although no correlation was found between the frequency and severity of cardiac arrhythmias and the neurological condition, the site and extent of intracranial blood on computed tomography scan, or the location of ruptured malformation, the extremely high incidence of cardiac arrhythmias, sometimes serious, in the acute period after subarachnoid haemorrhage and the absence of clinical and radiological predictors make systematic continuous ECG monitoring compulsory to improve the overall results of subarachnoid haemorrhage, irrespective of early or delayed surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that arrhythmias are associated with an increased risk of cardiovascular comorbidity, prolonged hospital stay and poor outcome or death after SAH, after adjusting for other predictors of poor outcome [22]. Although no correlation was found between the frequency and severity of cardiac arrhythmias and the neurological condition, the site and extent of intracranial blood on computed tomography scan, or the location of ruptured malformation, the extremely high incidence of cardiac arrhythmias, sometimes serious, in the acute period after subarachnoid haemorrhage and the absence of clinical and radiological predictors make systematic continuous ECG monitoring compulsory to improve the overall results of subarachnoid haemorrhage, irrespective of early or delayed surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac arrhythmias can occur as the fi rst symptom of acute SAH and are life threatening in 5-10 % of cases [ 27 ]. Major rhythmic abnormalities include sinus tachycardia, sinus bradycardia, and premature atrial and ventricular beats [ 25 ]. Myocardial injury is found in approximately 30-60 % of SAH patients and is associated with higher mortality [ 28 -30 ].…”
Section: Cardiac Complicationsmentioning
confidence: 99%
“…8 Alteration of rhythm and conduction have been detected in about 4% of patients with SAH, the most common arrhythmias are sinus bradycardia and atrial fibrillation/flutter (76% of arrhythmias observed by Frontera et al). 9 An electrocardiographic pattern was encountered in patients with cerebrovascular accidents which consisted primarily of T waves of large amplitude and duration. Large U waves were often present which may fuse in part or entirely within the T wave.…”
Section: Discussionmentioning
confidence: 99%